Decision model for the Arctic : cross-impact analysis - Sigurður Valur Guðmundsson 1984- (2014)
This research is on the field of decision analysis and decision making. It is a part of a larger project called “An open access decision model for strategic planning of the Arctic region” (DMA). The DMA project is arranged by CORDA (Centre of Risk and Decision Analysis), a division of the School of Science and Engineering at Reykjavík University. Purpose – The goal of the research is to collect data for a decision model for the Arctic region and to develop a working cross-impact analysis (CIA) method for future work of the DMA project. The model aims at assisting both the business segment and the government in making decisions regarding global warming and how the growing activities in the Arctic region can affect Icelandic economy in the near future. The economic parameters and the methodology used were developed in previous work of the DMA project. Approach – First, a thorough analysis of previous research was done to determine whether it was possible to continue the previous research where it left off. It was decided to continue where the former research ended but the internet survey needed to be done again. This was necessary because the sample of the survey was not large enough. Therefore, an internet survey was conducted with a larger sample. The purpose was to validate the findings of the previous research. Data was collected by sending an introductory letter via email which included a link to a questionnaire. Finally work was done to find an appropriate and working CIA method to find and calculate the cross-impact of the economic parameters for the DMA project. Appropriate method was found (CIA using GDSS) and the use of it demonstrated with the data from the internet survey. Findings – The data of the research suggest that the economic parameters found in the previous research will have some impact on the Icelandic economy in the next 20 years. Therefore these parameters can be used in the DMA project along with the data obtained from the surveys. The participants were asked how much impact a parameter ...